PENGARUH PEMBELAJARAN PEDAGOGI KEJURUAN TERHADAP KESIAPAN PROFESIONAL MENGAJAR MAHASISWA PENGENALAN LAPANGAN PERSEKOLAHAN (PLK) DI BIDANG TEKNIK MESIN - Fachrul Ihsan; Purwantono Purwantono; Ambiyar Ambiyar; Wanda Afnison; Raihan Ramadhan (Unversitas Negeri Padang, 2025)
The Vocational Pedagogy course is an important factor in supporting students' teaching readiness. Observation shows that PLK students have a gap in teaching readiness even though they have taken Vocational Pedagogy courses. This study describes the teaching readiness of students in the Mechanical Engineering Department at Padang State University and analyzes the effect of the course on teaching readiness. The study employed a causal quantitative approach, surveying 92 students from the 2020 and 2021 cohorts, selected via Proportionate Stratified Random Sampling. Data were collected via a questionnaire and analyzed using descriptive analysis and simple linear regression. The results showed that students' mastery of the Vocational Pedagogy course was high, with an average score of 4.5. Students' teaching readiness was also in the